Tarif Ideal Bus Trans Jakarta Berdasarkan Analisis Willingness To Pay dan Ability To Pay - Romadhona, Prima Juanita; Maimunah, Siti (Warta Penelitian Perhubungan, 2011)
Based on a suroey of YLKI (Indonesian Consumers Foundation), 2010 that less than 20% of TransJakarta's users has low income. The study is expected to get the ideal rate based on ability and willingness to pay of passengers. The result shows that the average WTP is Rp.4.760,and the average of ATP is Rp.5.013,-. Based on that, 73% (based on WTP) and 86% (by ATP) of the passengers have the ability to pay more than current rates. Keywords: TransJakarta, Willingness To Pay, Ability To Pay